Logistic Map-Based Banking Loan Dynamics with Central Bank Policies - Ansori, Moch. Fandi; Ashar, Nurcahya Yulian; Fata, Hafidh Khoerul (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we investigate the relationship between the dynamics of bank loans and several central bank policies, including reserve requirement, capital adequacy ratio, and deposit and loan benchmark interest rates. Using bifurcation analysis, we investigate the effect of loan stability on the policies resulting in transcritical and flip bifurcations. We validate the analytical results by presenting a one-parameter bifurcation diagram to see the impact of each policy and a two-parameter bifurcation diagram to examine the impact of the combination of two central bank policies on loan stability. In addition, we present a sensitivity analysis of the effect of the combination of two policies using a contour plot.